High-resolution TEM characterization of epitaxial passivation for a high nitrogen face-centered-cubic phase formed on AISI 304L austenitic stainless steel in borate buffer solution. (10th October 2021) - Tong, S.; Che, H.L.; Lei, M.K.
Highlights: Real-time nanostructure of passive film on γN phase is characterized by TEM/EDS. All passive films composed of defect spinels are epitaxially growing on γN phase. n -type inner (Fe, Cr)3 (N, O)4 and p -type outer γ -Fe2 (N, O)3 region in passive films. Low-defective passive film inhibits absorption of aggressive ion. Nanostructure of dense passive film limits migration of Cr 3+ ion and anion vacancy. Abstract: The real-time composition and structure of the passive film formed on a high nitrogen face-centered-cubic phase ( γN ) layer at the characterized transient corrosion currents from the electrochemical noise analyses in the borate buffer solution with the pH = 7.7 are investigated by the transmission electron microscope (TEM) with energy dispersion X-ray spectrum (EDS) using the focused ion beam (FIB) sampling. The thicker passive film of the γN phase layer on the nitrided AISI 304L in the borate buffer solutions is observed as two regions structure of O enriched n -type defect spinel γ -Fe2 (N, O)3 and hydroxides in the outer region and Cr and N enriched p -type defect spinel (Fe, Cr)3 (N, O)4 in the inner region, although few β -(Fe, Cr)OOH compounds are detected due to dehydration. The defect spinel in directions of < 112 >, < 213 > and < 110 > is epitaxially growing on the γN phase matrix during the passivation up to 8 h with a decreasing lattice mismatch from 5.9 to 1%, which is attributed to lattice expansion of the γN phase and the defect spinel. The lattice expansion of the γN phase at the interface with growing passive film is affected by dissolving nitrogen outward to the borate buffer solution. The dissolving nitrogen in the defect spinel induces its lattice expansion by hydrolysis at the interface. The dense and low-defective passive films on the γN phase layer have a significant effect on the corrosion resistance due to inhibition of the absorption of aggressive ion and limitation of the carrier density. Graphical abstract: Image, graphical abstract